2019
DOI: 10.35631/ijmoe.12004
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Willingness to Contribute for Waqf Education

Abstract: Nowadays, education has become more complex than before. The need for knowledge, understanding, and passion among societies had caused an increase in education demand. To prepare a better and higher-level quality of education, the Ministry of Higher Education had played vital roles to enhance their services and efficiency levels. Nevertheless, the trend of budget allocation for operating expenditure in education sectors had shown a decline for the past three years, starting from the year 2016 until 2018 (Minis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…This study uses subjects from various societal backgrounds and uses a quantitative design that uses statistical analysis tools. This study investigates the relationship between cash waqf literacy and people's desire for cash waqf, as shown by Laila et al, (2023); Kasri & Chaerunnisa, (2022); Chalabi & Moutahaddib, (2020); Abd Aziz & Noh, (2019); Muhammad et al, 2023;Indahsari et al, 2020;andMuhammad et al, (2023)., 2014;Shukor et al, 2017., Amin et al, (2013, Baskoroputra, (2019), Fauziah & Elayuby (2019, Cupian et al (2020, Maswan Amin (2021, (Witjaksono, 2018), Amin & Rohman (2021). Ahmad et al (, 2014.).…”
Section: Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study uses subjects from various societal backgrounds and uses a quantitative design that uses statistical analysis tools. This study investigates the relationship between cash waqf literacy and people's desire for cash waqf, as shown by Laila et al, (2023); Kasri & Chaerunnisa, (2022); Chalabi & Moutahaddib, (2020); Abd Aziz & Noh, (2019); Muhammad et al, 2023;Indahsari et al, 2020;andMuhammad et al, (2023)., 2014;Shukor et al, 2017., Amin et al, (2013, Baskoroputra, (2019), Fauziah & Elayuby (2019, Cupian et al (2020, Maswan Amin (2021, (Witjaksono, 2018), Amin & Rohman (2021). Ahmad et al (, 2014.).…”
Section: Research Resultsmentioning
confidence: 99%
“…It is very important for the public to study waqf as a source of knowledge about waqf to realize and optimize the potential of waqf, especially cash waqf; It is hoped that by knowing a lot about waqf and the essence of cash waqf, people will be more interested in carrying out cash waqf (Imsar et al, 2021). Scoping review studies (Kasri & Chaerunnisa, 2022), (Abd Aziz & Noh, 2019), (Laila et al, 2023), Maswan Amin (2021), and Cupian et al (2020) shows that interest in cash waqf is influenced by knowledge about cash waqf. Thus, these findings support the idea that good cash waqf literacy in society can increase cash waqf income.…”
Section: Discussionmentioning
confidence: 99%
“…The word Waqf originated from an Arabic word 'waqafa' -meaning to hold, to confine, and to stop while in Shariah, waqf means voluntary, permanent, or irrevocable dedication of a portion of one's wealthin cash or kind -to Allah (Abd Aziz & Noh, 2019;Kahf, 1999;Mohsin, 2013;Shukor, Anwar, Aziz, & Sabri, 2017). Waqf has been defined in many ways over the years by scholars of Islamic finance.…”
Section: Understanding Waqfmentioning
confidence: 99%
“…Awareness is also seen as a crucial factor influencing willingness and perception of Muslims to contribute to waqf and engage in waqf activities. Abd Aziz and Noh (2019) stress that people who are better informed about waqf will guide them to improve their efforts in donating more to the society. Again, Arum et al (2018) found that Muslim with sound financial literacy skills may separate investments that include prohibited features, like usury and resort to waqf.…”
Section: The Awareness and Perception Of Waqfmentioning
confidence: 99%
“…Ridhwan et al (2014) found that a low level of awareness is one of the factors contributing to the reason why Islamic financial planning is not widely practiced among Muslim countries. Similarly, Abd Aziz and Noh (2019) state that in an attempt to raise awareness of waqf among Muslims as a poverty reduction tool reveal that inadequate knowledge and lack of awareness on waqf is a barricade to explore waqf potential. This finding is supported by Faiz (2014) who said that there is still a lack of awareness to contribute to waqf among a majority of Muslims.…”
Section: The Awareness and Perception Of Waqfmentioning
confidence: 99%